Thalassiosira spp. community composition shifts in response to chemical and physical forcing in the northeast Pacific Ocean - Chappell, Phoebe D.; Whitney, LeAnn; Haddock, Traci L.; Menden-Deuer, Susanne; Roy, Eric G.; Wells, Mark; Jenkins, Bethany D. (Frontiers in Microbiology, 2013)
Diatoms are genetically diverse unicellular photosynthetic eukaryotes that are key primary producers in the ocean. Many of the over 100 extant diatom species in the cosmopolitan genus Thalassiosira are difficult to distinguish in mixed populations using light microscopy. Here we examine shifts in Thalassiosira spp. composition along a coastal to open ocean transect that encountered a three-month-old Haida eddy in the northeast Pacific Ocean. To quantify shifts in Thalassiosira species composition, we developed a targeted automated ribosomal intergenic spacer analysis (ARISA) method to identify Thalassiosira spp. in environmental samples. As many specific fragment lengths are indicative of individual Thalassiosira spp., the ARISA method is a useful screening tool to identify changes in the relative abundance and distribution of specific species. The method also enabled us to assess changes in Thalassiosira community composition in response to chemical and physical forcing. Thalassiosira spp. community composition in the core of a three-month-old Haida eddy remained largely (>80%) similar over a two-week period, despite moving 24 km southwestward. Shifts in Thalassiosira species correlated with changes in dissolved iron (Fe) and temperature throughout the sampling period. Simultaneously tracking community composition and relative abundance of Thalassiosira species within the physical and chemical context they occurred allowed us to identify quantitative linkages between environmental conditions and community response.